Effect of Product Quality and Service Quality on Customer Loyalty Mediated by Customer Satisfaction - Ari Soetiyani; Rosariah Apriani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
UD Ikan Catfish in Bekasi is a trading business that sells catfish, which is a business engaged in the trade of catfish. UD Ikan Lele in Bekasi to improve customer satisfaction in the trading business, entrepreneurs must improve product quality and service quality in serving customers. The formulation of the problem in this study is how to manage the catfish trading business in Bekasi to increase customer satisfaction which can have a positive impact on increasing customer loyalty. The population in this study are consumers from various circles from students to housewives, where the sampling technique uses Simple Random Sampling and the number of samples is 140 respondents. The data analysis technique used is 2-stage multiple linear regression. Based on the results of the analysis, it can be seen that the calculated t value for product quality (2.369) and service quality (5.511) variables > t table 1.960, so that product quality and service quality partially have a positive and significant effect on customer satisfaction. Product quality and service quality simultaneously have a positive and significant effect on customer satisfaction, because the calculated F value is 49.610 > F table 3.00. calculated t value of the unstandardized predicted value variable is customer satisfaction 12.632 > t table 1.960, so that customer satisfaction has a positive and significant effect on customer loyalty.